Sejarah, Struktur dan Teologi Doa Syukur Agung Ketiga Tata Perayaan Ekaristi 2020: Visi Manajemen dan Kepemimpinan Pastoral - Vries, Richardo Martin Emmanuel de; Prayidno, Iswadi (Felicitas, 2024)
This article is entitled "History, Structure and Theology of the Third Eucharistic Prayer for the 2020 Eucharistic Celebration: Pastoral Vision Management and Leadership." This article aims to provide a deeper understanding of the development, structure and theological significance of the third Eucharistic Prayer in the 2020 Eucharistic Celebration. This paper focuses on selecting the Third Eucharistic Prayer as the main study, based on the idea of the Liturgy as the source and pinnacle of Church life as described in the Sacrosanctum Concilium (SC) n. 10. Liturgy is not only a formal ritual of worship, but also the core of the identity and mission of the Catholic Church which drives and gives meaning to all ecclesiastical activities. Thus, this paper tries to explain the inspirations originating from liturgical texts, especially DSA III, which can be applied in the pastoral work of the Catholic Church. This paper aims to create bridge between liturgical theology and its application in a concrete pastoral context. By exploring the meaning of DSA III, we can find inspiration that can help direct the Vision Management and Pastoral Leadership of the Catholic Church. Indeed, the inspiration for the Vision Management and Pastoral Leadership of the Catholic Church can be found in various sources, including the Holy Bible and the teachings of the Church Fathers, but this paper is a simple effort that tries to highlight the potential contained in DSA III, a prayer that is very often used in celebration of the Eucharist on Sunday by the faithful. In this research it was found that DSA III contains some key values that can be applied in management and pastoral leadership within a parish. Thus, DSA is also a series of prayers which are intended to be prayed and absorbed together by the priest and the congregation. More than that, DSA is not limited to a series of prayers that stop at the Eucharistic liturgy. DSA is also lived out in daily activities, especially when people gather together at church to be involved in church services.